2012
DOI: 10.1186/1471-2334-12-134
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of community-acquired pneumonia in a population-based study: Link between etiology and patients characteristics, process-of-care, clinical evolution and outcomes

Abstract: BackgroundThe etiologic profile of community-acquired pneumonia (CAP) for each age group could be similar among inpatients and outpatients. This fact brings up the link between etiology of CAP and its clinical evolution and outcome. Furthermore, the majority of pneumonia etiologic studies are based on hospitalized patients, whereas there have been no recent population-based studies encompassing both inpatients and outpatients.MethodsTo evaluate the etiology of CAP, and the relationship among the different path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
3
8

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 32 publications
6
52
3
8
Order By: Relevance
“…Atypical pathogens and mixed infections are also significant causes with detectable rates standing at 18% and 14% respectively. Also in Spain, Alberto Capelastegui and his colleagues discovered a 50% detectable rate in a prospective study (24). Atypical pathogens were significantly more frequent among outpatients (67%), than among inpatients(30.6%).…”
Section: Prevalence Of Atypical Pneumoniamentioning
confidence: 99%
“…Atypical pathogens and mixed infections are also significant causes with detectable rates standing at 18% and 14% respectively. Also in Spain, Alberto Capelastegui and his colleagues discovered a 50% detectable rate in a prospective study (24). Atypical pathogens were significantly more frequent among outpatients (67%), than among inpatients(30.6%).…”
Section: Prevalence Of Atypical Pneumoniamentioning
confidence: 99%
“…These microorganisms might cause severe CAP in approximately 1-7 % [11][12][13]. A retrospective study of 11 patients with ARDS showed that six out of 11 pneumonia cases were caused by C. pneumoniae, and mortality was 100 % in the group of patients with a CURB-65 score of 2 or higher [14].…”
Section: Introductionmentioning
confidence: 99%
“…Высокая заболеваемость и смертность при внебольничной пневмонии определяют необхо-димость дальнейших углубленных исследований ме-ханизмов развития и прогрессирования заболевания, поиска путей оптимизации диагностики и терапии. Механизмы развития внебольничных пневмоний раз-нообразны и зависят как от возбудителя, так и от путей проникновения инфекции в легкие [8]. Однако не вы-зывает сомнения ведущая роль свободнорадикального окисления как в развитии, так и в усугублении пато-логического процесса, и вовлеченность в него эритро-цитов.…”
Section: Introductionunclassified